1998
DOI: 10.1046/j.1365-2036.1998.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 24‐h control of gastric acidity by three different dosages of pantoprazole in patients with duodenal ulcer

Abstract: INTRODUCTIONMany clinical studies support the relationship between acid suppression and healing of duodenal ulcer and re¯ux oesophagitis.1, 2 Moreover, proton pump inhibitors represent a central component of numerous triple therapies against Helicobacter pylori infection.3 A recent Consensus Meeting held in Maastricht 4 has recommended twice daily doses of proton pump inhibitors combined with two antibiotics for 1 week as the best treatment to cure the infection. In relation to the above wide range of indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The prevalence of gastric H. pylori infection, a factor improving the response to proton pump inhibitors, 20 was comparable in the two groups, as was the prevalence of atypical manifestations of GERD, such as non‐cardiac chest pain and respiratory symptoms, conditions for which higher doses of proton pump inhibitors for acid suppression are often needed 8 , . 18 , 21–23 In our series, a double‐dose regimen of lansoprazole or omeprazole produced normalization of oesophageal acid exposure in all patients with persisting abnormal acid reflux while on a single‐dose regimen, in accordance with previous studies showing the dose–response relationship of proton pump inhibitors to gastric acid antisecretory effects 24–26 …”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of gastric H. pylori infection, a factor improving the response to proton pump inhibitors, 20 was comparable in the two groups, as was the prevalence of atypical manifestations of GERD, such as non‐cardiac chest pain and respiratory symptoms, conditions for which higher doses of proton pump inhibitors for acid suppression are often needed 8 , . 18 , 21–23 In our series, a double‐dose regimen of lansoprazole or omeprazole produced normalization of oesophageal acid exposure in all patients with persisting abnormal acid reflux while on a single‐dose regimen, in accordance with previous studies showing the dose–response relationship of proton pump inhibitors to gastric acid antisecretory effects 24–26 …”
Section: Discussionsupporting
confidence: 89%
“…0.05) between the duration of acid suppression and the proportion of healed (duodenal) ulcers', which both dose-dependently increased from 10 to 20 and further to 40 mg omeprazole over 4 weeks. The same dose-response relationship has been reported for pantoprazole in DU patients [137] and in pH-metry studies [112][113][114][115].…”
Section: Ppis Show Similar Dose-response Relationshipssupporting
confidence: 57%
“…The lower night‐time pH relative to daytime values is a common finding, which has been reported previously in both patients and healthy volunteers taking proton pump inhibitors 22–26 . It has been suggested that, at least for omeprazole, the magnitude of the nocturnal acid breakthrough may be dependent upon the dosing regimen, with an evening dose resulting in less breakthrough than a morning dose 24 .…”
Section: Discussionmentioning
confidence: 62%